Residential proximity to oil and gas production sites and hematologic malignancies: A case‐control study. Issue 12 (17th October 2022) - Forster, Felix; Herrera, Ronald; Hoopmann, Michael; Kieschke, Joachim; Deitermann, Bernhilde; Radon, Katja
Abstract: Background: We investigated the association between residential proximity to oil and gas production sites and hematologic malignancies, due to a cancer cluster in the German state of Lower Saxony. Methods: A registry‐based case‐control study was conducted including 3978 cases of hematologic malignancies diagnosed within 2013–2016 and 15, 912 frequency‐matched controls randomly drawn by population registries. Residential proximity to 5333 oil and gas production sites at the time of diagnosis was calculated. Unconditional logistic regression models were used to estimate the association between living within 1 km of any exposure site and developing a hematologic malignancy. Models were adjusted for matching variables sex, age group, district, and year of diagnosis as well as for proximity to main streets and to agricultural land. Results: We found no association between the development of hematologic malignancies and the proximity to all oil and gas production sites (odds ratio: 0.97; 95% confidence interval: 0.85, 1.11). Focusing on gas production sites increased the odds of developing hematologic cancer (odds ratio: 1.19; 95% confidence interval: 0.97, 1.45). In stratified analyses, associations were stronger in women and for acute myeloblastic leukemia. We also found an association in the district where the initial cluster occurred. Conclusions: Our results suggest that residential proximity to oil and gas production is not a risk factor for all hematologic malignancies in general. Sporadic and past exposures are the most likely scenarios for mechanisms involving oil and gas production, leading to increased risk for certain subtypes of cancer in certain populations.